2011
DOI: 10.1177/1354068811411026
|View full text |Cite
|
Sign up to set email alerts
|

Analysing multiparty competition in plurality rule elections

Abstract: Abstract:The study of general election outcomes can be helped by finding better approaches for visualizing large quantities of information and asking questions about its patterning. We review the Nagayama or 'all possibilities' triangle display, and show that it can only be legitimately used to show an overall 'field' of results that is logically feasible, called the effective space of competition, which varies with the number of observable parties. We apply this reductionist view to analyse outcomes in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…I have implemented some minor consistency and ENPv calculation corrections to the original data. I also thank Rekha Diwakar of the University of Sussex for the India data here, drawn from Dunleavy and Diwakar (2013). Naturally all interpretations of any of this data are mine alone.…”
Section: Acknowledgementsmentioning
confidence: 95%
See 1 more Smart Citation
“…I have implemented some minor consistency and ENPv calculation corrections to the original data. I also thank Rekha Diwakar of the University of Sussex for the India data here, drawn from Dunleavy and Diwakar (2013). Naturally all interpretations of any of this data are mine alone.…”
Section: Acknowledgementsmentioning
confidence: 95%
“…In fact, we know empirically that this is perverse -that in the most conventionally recognized two-party system, the United States, very high levels of P 1 2 P 2 leads routinely occur, and only a tiny fraction of results empirically occur at P 1 2 P 2 leads below 5%, as Table 4 demonstrates. Now there are good reasons for believing that in party system evolution terms (as in so many other respects) the United States may be an exceptional case, a strangely "frozen", super-Duvergerian party system still showing remarkably few of the multi-partism trends characteristic of most large and modern liberal democracies (see Dunleavy & Diwakar, 2013). Yet Table 4 shows that Ghana and Bangladesh have more districts than the United States where P 1 2 P 2 leads are below 5%.…”
Section: The T Index Is An Internally Complex Measure and Misreads Twmentioning
confidence: 96%
“…Some empirical studies (Gaines 1999;Diwakar 2007;Chytilek 2007;Grofman et al 2009;Dunleavy -Diwakar 2011) found various violations of the Duvergerian assumptions at the level of individual countries (e.g., India, Canada, UK, USA). However, a recent analysis working with large data sets of elections in SMDs confirmed that district magnitude had (at the district level) the effect that Duverger had expected, although the effect of electoral institutions could be contingent on and (at the district level) inhibited by country-specific conditions such as social cleavages that generate demand for additional parties.…”
Section: Theoretical Framework: 'Micro-duvergerian' Agenda and Stratementioning
confidence: 99%
“…Equally, local politics and voting patterns are very different from national ones. So, it is possible to identify a far greater contribution of these “radical third party” elements at local Council level than through Parliamentary constituencies (Dunleavy & Diwakar, ).…”
Section: The Political Economy Confluence Of Green Politics and Businessmentioning
confidence: 99%